Efficacy of Tribulus terrestris on diabetes and sexual disorders: A narrative review - Salwa Bouabdallah; Mossadok Ben-Attia; Omayma A Eldahshan (BIORE Scientia Publisher, 2024)
Tribulus terrestris L. (T. terrestris) is widely distributed worldwide (Australia, Europe, India, North Africa). It typically contains a substantial amount of active ingredients, especially saponins, alkaloids, flavonoids, tannins, terpenoids, and phenol carboxylic acids. Additionally, T. terrestris has been frequently used in folk medicine and as a food supplement, highlighting the importance of evaluating its phytopharmacological properties. Various hypotheses suggest that this species may have significant potential in preventing and improving various human conditions, including diabetes, inflammatory diseases, low sexual desire, and infertility. Phytochemical studies reveal a significant disparity in the content of active substances, with a notable gap in the concentrations of spirostanol saponins and furostanol, which are the predominant active ingredients associated with therapeutic effects. The objective of this present review is to evaluate T. terrestris -based formulations by exploring various potential mechanisms of action, aiming to determine whether the use of T. terrestris supplements is justified in the context of diabetes and its complications.